Towards sustainable mining: exploiting raw materials from extractive waste facilities - Dino, Giovanna Antonella; Cavallo, Alessandro; Rossetti, Piergiorgio; Garamvölgyi, Ernő; Sándor, Renáta; Coulon, Frederic (MDPI, 2020)
The focus of the present research is on the exploitation of extractive waste to recover raw materials, considering the technological and economic factors, together with the environmental impacts, associated with extractive waste quarrying and dressing activities. The present study, based on a case history from Northern Italy (Montorfano and Baveno granite quarrying area), was intended to validate the presented interdisciplinary approach for evaluating economic and environmental impacts associated with extractive waste facility exploitation (from granite waste to products for the ceramic industry and by-products for the building industry). A shared methodology was applied to determine extractive waste characteristics (geochemistry, petrography, and mineralogy), waste volume (geophysical, topographic, and morphologic 3D characterization) and potential exploitable products and by-products. Meanwhile, a Life Cycle Assessment (LCA) was applied to determine the environmental impacts associated with the extraction and processing phases.
Keywords: granite waste; feldspar production; REE; LCA; circular economy; sustainable mining